Torsion of an Accessory Liver Lobe in a Newborn - Krause, Tobias; Cholewa, Dietmar; Liniger, Benjamin; Berger, Steffen; Milosevic, Milan (European Journal of Pediatric Surgery Reports, 2024)
Accessory liver lobes are rare. We present the rare case of torsion of an accessory liver lobe in a neonate.A 13-day-old newborn presented with failure to thrive and hematemesis without fever. The initial workup with sonography, magnetic resonance imaging, and upper gastrointestinal study was suspicious of a duplication cyst, most likely in the posterior wall of the stomach. Laboratory and radiological findings were not suggesting a choledochal cyst. We performed a laparotomy with resection of the 3.2 × 2.1 × 1.1 cm mass. Intraoperatively, the cystic formation extended from of the liver bed up to the lesser curvature of the stomach. The mass was attached to the left liver lobe with fibrous bands. Histopathology revealed necrotic liver parenchyma with patent viable biliary ducts, indicative of an accessory liver lobe that underwent torsion in the perinatal period. The postoperative course and follow-up (6 months so far) were uneventful. To our knowledge, this is the youngest described patient in the literature with an accessory liver lobe torsion and the second case report concerning this entity in a neonate. It presents an extremely rare differential diagnosis in symptomatic neonates with a cystic mass in the upper abdomen.
Keywords: accessory liver lobe torsion; hepatic lobe; neonatal liver lobe torsion; pedunculated liver lobe